Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Diurnal temperature fluctuations drive compartment-specific microbial dynamics in tissue and skeleton of Stylophora pistillata from marginal reefs - Jia-Min Kao; Chih-Ying Lu; Sen-Lin Tang; Shinya Shikina; Sung-Yin Yang; Shan-Hua Yang (Marine Environmental Research, 2026)

Association between lipid oxidation, water activity and aflatoxin B1 risk reversal in stored sunflower seeds: A storage microenvironment observation study - Sen Zeng; Jiamin Song; Xuan Ou; Tinyan Sang; Siying Lin; Ruixia Zhang; Jie Chen; Yuhua Tang; Songlei Wang; Yanan Sun (Journal of Stored Products Research, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Oyster-derived Zinc Exhibits Superior Anti-anemic Efficacy and Bioavailability Compared with Conventional Zinc Supplements - Yen-Hua Chen; Hui-Lin Feng; Jia-Ling Tang; Chen-Wei Chang; Sen-Shyong Jeng (Biological Trace Element Research, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Metabolic model-guided strain design for improved succinic acid production in Yarrowia lipolytica - Wentao Tang; Sen Lin; Guanghao Chen; Tianwei Hao (Bioresource Technology, 2026)

First report of Thraustochytrium caudivorum isolated from the undulated surf clam (Paratapes undulatus): Morphological, molecular, and ecological insights under climate change - Yu Chen; Seung-Hyeon Kim; Jinxia Long; S.D.N.K. Bathige; Hyoun Joong Kim; Sen-Lin Tang; Kyung-Il Park (Protist, 2025)

Photocatalytic of hydrogen peroxide production on chelating agent decorated zinc cadmium sulfide@halloysite hybrid - Sen Lin; Shiyong Sun; Jun Liu; Xiang Li; Haoming Tang; Lin Gong; Xingyun Yang (Journal of Environmental Chemical Engineering, 2025)

Chromosome-level genome assembly reveals divergent immune mechanisms in the genus Meretrix - Che-Chun Chen; Te-Hua Hsu; Hsin-Yun Lu; Sen-Lin Tang; Ying-Ning Ho (Fish & Shellfish Immunology, 2025)

Bacterial community formation on plastic and glass in coral reefs - Yusuke Iwaki; Kohei Hamamoto; Fabian Gösser; Chengze Li; Jeffrey Jolly; Sen-Lin Tang; Timothy Ravasi; James Davis Reimer (Coral Reefs, 2025)

Induced bleaching enhances cold tolerance in coral larvae: a potential strategy for cryopreservation optimization - Federica Buttari; Arah Narida; Sujune Tsai; Cheng-Liang Huang; Zhi-Hong Wen; Sen-Lin Tang; Chiahsin Lin (Coral Reefs, 2025)

Synthesis of novel thiol-functionalized halloysite nanotube/ organophyllosilicate composite for efficient removal of aqueous U(VI) - Edward Opong Acheampong; Ke Wang; Haoming Tang; Sen Lin; Shiyong Sun (Journal of Environmental Chemical Engineering, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Structural analysis and numerical modeling of multi-stage tectonic deformation in the Ziliujing anticline, SW Sichuan Basin, China: Implications for deformation propagation in salt-bearing fold-and-thrust belts - Jiawei Liu; Gang Rao; Sen Bai; Xiaolin Xiong; Jinwu Zhang; Wenxiong Yang; Chao Yin; Yaqi Zhong; Pengcheng Tang; Jianhua Qiu; Lin Gao (Tectonophysics, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

1DCNN-based prediction methods for subsequent settlement of subgrade with limited monitoring data - Sen-Lin Xie; Anfeng Hu; Meihui Wang; Zhi-Rong Xiao; Tang Li; Chi Wang (European Journal of Environmental and Civil Engineering, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Identification of forest priority conservation and restoration areas for different SSPs-RCPs scenarios - Miaomiao Liu; Shuang Liu; Raohan Tang; Minggao Liu; Xisheng Hu; Sen Lin; Zhilong Wu (Journal of Environmental Management, 2025)

Echelon extraction of valuable components from salt lake brine substrate - Xiangting Tang; Jun Chen; Ye Zhang; Jianguo Yu; Sen Lin (Desalination, 2025)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Valuable components recovery from wastewater and brine using electrocoagulation-based coupled process: A systematic review - Ye Zhang; Xiangting Tang; Jiayi Zhang; Yi Zhang; Ruoning Yu; Wenshuo Wang; Sen Lin; Jianguo Yu (Desalination, 2024)

First discovery of impact-induced vapor deposition of native copper, FeCo alloy and digenite from Chang'e-5 lunar soil - Jing Li; Lixin Gu; Xu Tang; Xiaoying Liu; Sen Hu; Yangting Lin (Icarus, 2024)

First classification of iron meteorite fragment preserved in Chang’e-5 lunar soils - Xiaoying Liu; Lixin Gu; Heng-Ci Tian; Jing Li; Xu Tang; Sen Hu; Yangting Lin (Science Bulletin, 2024)

Rediscovery of Seriatopora corals in shallow reefs of Okinawa Island, Japan - Hideyuki Yamashiro; Sen-Lin Tang (Regional Studies in Marine Science, 2024)

Sulfur bacteria-reinforced microbial electrochemical denitrification - Sen Lin; Wentao Tang; Yihang Xiao; Feixiang Zan; Xiaoming Liu; Guanghao Chen; Tianwei Hao (Bioresource Technology, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A novel methodological framework for risk zonation and source–sink response concerning heavy-metal contamination in agroecosystems - Lian Chen; Shenglu Zhou; Cuiming Tang; Guoqing Luo; Zhenjiang Wang; Sen Lin; Jianwu Zhong; Zhiyi Li; Yuan Wang (Science of The Total Environment, 2023)

Bile acids and their receptors in regulation of gut health and diseases - Sen Lin; Sutian Wang; Peng Wang; Cuiming Tang; Zhenjiang Wang; Lian Chen; Guoqing Luo; Hong Chen; Yuntao Liu; Bin Feng; De Wu; Douglas G. Burrin; et al. (Progress in Lipid Research, 2023)

Migration, Health Risks, and Source Apportionment of Heavy Metals in Agricultural Soil–Dustfall–Crop Systems in a Typical Watershed of the Taihu Region, China - Lian Chen; Shenglu Zhou; Cuiming Tang; Guoqing Luo; Zhenjiang Wang; Sen Lin; Jianwu Zhong; Zhiyi Li; Yuan Wang (Water, Air, & Soil Pollution, 2023)

A multi-step nitrifying microbial enrichment to remove ammonia and nitrite in brackish aquaculture systems - Dao Thi Anh Tuyet; Le Minh Hiep; Ha Thi Binh; Le Thanh Huyen; Sen-Lin Tang; Pei-Wen Chiang; Do Manh Hao (Biodegradation, 2022)

Analysis of the influence of reinforcement material type on bearing and deformation characteristics of reinforced earth retaining wall - Jia-Quan Wang; Sen-Lei Hou; Zhi-Nan Lin; Yi Tang (Arabian Journal of Geosciences, 2022)

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Phylogeography of Blue Corals (Genus Heliopora) Across the Indo-West Pacific - Hiroki Taninaka; Davide Maggioni; Davide Seveso; Danwei Huang; Abram Townsend; Zoe T. Richards; Sen-Lin Tang; Naohisa Wada; Taisei Kikuchi; Hideaki Yuasa; Megumi Kanai; Stéphane De Palmas; et al. (Frontiers in Marine Science, 2021)
Species delimitation of corals is one of the most challenging issues in coral reef ecology and conservation. Morphology can obscure evolutionary relationships, and molecular datasets are consistently revealing greater within-species diversity than currently understood. Most phylogenetic studies, however, have examined narrow geographic areas and phylogeographic expansion is required to obtain more robust interpretations of within- and among- species relationships. In the case of the blue coral Heliopora , there are currently two valid species ( H. coerulea and H. hiberniana ) as evidenced by integrated genetic and morphological analyses in northwestern Australia. There are also two distinct genetic lineages of H. coerulea in the Kuroshio Current region that are morphologically and reproductively different from each other. Sampling from all Heliopora spp. across the Indo-Pacific is essential to obtain a more complete picture of phylogeographic patterns. To examine phylogenetic relationships within the genus Heliopora , we applied Multiplexed inter simple sequence repeat (ISSR) Genotyping by sequencing (MIG-seq) on > 1287 colonies across the Indo-West Pacific. Maximum likelihood phylogenetic trees indicated the examined Heliopora samples comprise three genetically distinct groups: H. coerulea group, H. hiberniana group, and a new undescribed Heliopora sp. group with further subdivisions within each group. Geographic structuring is evident among the three species with H. hiberniana group found in the Indo-Malay Archipelago and biased toward the Indian Ocean whilst Heliopora sp. was only found in the Kuroshio Current region and Singapore, indicating that this taxon is distributed in the western Pacific and the Indo-Malay Archipelago. Heliopora coerulea has a wider distribution, being across the Indian Ocean and western Pacific. This study highlights the effectiveness of phylogenetic analysis using genome-wide markers and the importance of examining populations across their distribution range to understand localized genetic structure and speciation patterns of corals.

Monthly progression rates of the coral-killing sponge Terpios hoshinota in Sesoko Island, Okinawa, Japan - Siti N. Aini; Sen-Lin Tang; Hideyuki Yamashiro (Coral Reefs, 2021)

Effects of Ocean Acidification on Coral Endolithic Bacterial Communities in Isopora palifera and Porites lobata - Sung-Yin Yang; Chih-Ying Lu; Sen-Lin Tang; Rocktim Ramen Das; Kazuhiko Sakai; Hideyuki Yamashiro; Shan-Hua Yang (Frontiers in Marine Science, 2020)
Endolithic microbes in coral reefs may act as a nutrient source for their coral hosts. Increasing atmospheric CO 2 concentrations are causing ocean acidification (OA), which may affect marine organisms and ecosystems, especially calcifying organisms such as reef-building corals. However, knowledge of how OA affects marine microbes remains limited, and little research has been done on how coral endolithic communities respond to shifting environmental baselines. In this study, the endolithic communities of two common shallow water coral species, Isopora palifera and Porites lobata , were examined to investigate the microbial community dynamics under OA treatments. The colonies were placed in an environment with a partial pressure of carbon dioxide ( p CO 2 ) of 1,000 or 400 ppm (control) for 2 months. Several I. palifera colonies bleached and died at 1,000 ppm p CO 2 , but the P. lobata colonies remained unaffected. Inversely, the endolithic community in P. lobata skeletons showed significant changes after OA treatment, whereas no significant dynamics were observed among the I. palifera endoliths. Our findings suggest that the skeletal structures of different coral species may play a key role in corals host and endoliths under future high-OA scenarios.

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

Coralloluteibacterium stylophorae gen. nov., sp. nov., a new member of the family Lysobacteraceae isolated from the reef-building coral Stylophora sp. - Wen-Ming Chen; Pei-Bei Xie; Sen-Lin Tang; Shih-Yi Sheu (Archives of Microbiology, 2018)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Bacteria associated with an encrusting sponge ( Terpios hoshinota ) and the corals partially covered by the sponge - Sen‐Lin Tang; Mei‐Jhu Hong; Ming‐Hui Liao; Wann‐Neng Jane; Pei‐Wen Chiang; Chung‐Bin Chen; Chaolun A. Chen (Environmental Microbiology, 2011)
Summary Terpios hoshinota , a dark encrusting sponge, is known to be a competitor for space in coral reef environments, and facilitates the death of corals. Although numerous cyanobacteria have been detected in the sponge, little is known of the sponge‐associated bacterial community. This study examined the sponge‐associated bacterial community and the difference between the bacterial communities in the sponge and the coral partially covered by the sponge by analysis of 16S rRNA gene sequences of samples isolated from the sponge covering the corals Favia complanata, Isopora palifera, Millepora sp. , Montipora efflorescens and Porites lutea . The sponge‐associated bacterial community was mainly (61–98%) composed of cyanobacteria, with approximately 15% of these alphaproteobacteria and gammaproteobacteria, although the proportions varied in different sponge samples. The dominant cyanobacteria group was an isolated group closely related to Prochloron sp. The comparison of the bacterial communities isolated from sponge‐free and the sponge‐covered P. lutea showed that covering by the sponge caused changes in the coral‐associated bacterial communities, with the presence of bacteria similar to those detected in black‐band disease, suggesting the sponge might benefit from the presence of bacteria associated with unhealthy coral, particularly in the parts of the coral closest to the margin of the sponge.

Evolution of DNA Polymerase Families: Evidences for Multiple Gene Exchange Between Cellular and Viral Proteins - Jonathan Filée; Patrick Forterre; Tang Sen-Lin; Jacqueline Laurent (Journal of Molecular Evolution, 2002)